2013
DOI: 10.1002/ijc.28394
|View full text |Cite
|
Sign up to set email alerts
|

DW MRI at 3.0 T versus FDG PET/CT for detection of malignant pulmonary tumors

Abstract: Emerging evidence suggests that diffusion-weighted magnetic resonance imaging (DW MRI) could be useful for tumor detection with N and M staging of lung cancer in place of fluorine 18 fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT). DW MRI at 3.0 T and FDG PET/CT were performed before therapy in 113 patients with pulmonary nodules. Mean apparent diffusion coefficient (ADC), maximal standardized uptake value (SUVmax ) and Ki-67 scores were assessed. Quantitatively, specificity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…The model yielded an average adjusted estimate of sensitivity of 89% (95% CI, 87%-91%) and specificity of 75% (95% CI, 71%-78%) (Figure 2) 30-89 .…”
Section: Resultsmentioning
confidence: 99%
“…The model yielded an average adjusted estimate of sensitivity of 89% (95% CI, 87%-91%) and specificity of 75% (95% CI, 71%-78%) (Figure 2) 30-89 .…”
Section: Resultsmentioning
confidence: 99%
“…5 ADC values also correlate with tumour grades. 4,17,18 Recent studies have shown that ADC may be more useful than FDG-PET in the differentiation of malignant tumours from benign lesions 3,6 and the new approaches using PET\MRI may provide more promising results in the future. 33 Among primary lung cancers, ADC values are usually low in cases with small cell carcinomas, but the values for adenocarcinomas and squamous cell carcinomas are usually similar.…”
Section: Discussionmentioning
confidence: 99%
“…It has been increasingly used for the detection, differential diagnosis and evaluation of tumour characteristics, including grading and prediction of the therapeutic response. [1][2][3][4][5][6][7] DW-MRI is a functional imaging technique that reveals physiological information by quantifying the diffusion of water molecules in tissues. The extent of this diffusion is measured using the apparent diffusion coefficient (ADC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Qualitative and quantitative assessments of the tumor were also higher with DWI than with PET/CT. 24 The detection rate depends on the b value, with lower SI at higher b values, which makes detection of ground-glass nodules difficult at higher b values (1000 s/mm 2 ). 20 However, a study on 25 patients showed that DWI as a part of WB-[ 18 F]-FDG-PET/MRI did not improve lesion detection.…”
Section: Nodule Sizementioning
confidence: 99%